Analysis of the Difference in Stock Prices Before and After the Cum-Ex Right Issue in 2024 - Febrina Almurdi, Suci; Zulfitra, Zulfitra; Sahroni, Sahroni (Lafadz Jaya Publisher, 2025)
This study examines whether stock prices differ before and after the cum-rights and ex-rights dates of rights issues conducted in 2024. Using a quantitative event-study design, we compile daily closing-price data for all issuers that executed rights issues in 2024. From 16 issuers, five banking firms are selected through purposive sampling. Differences in prices across the pre- and post-event windows are tested with the Wilcoxon signed-rank test, followed by a dummy-variable regression to estimate the magnitude and direction of change. The results indicate statistically significant price differences around the cum-ex rights issue period, implying that the market reacts to publicly available rights issue information. Overall, prices adjust after the event, consistent with semi-strong market efficiency and the dilution/price-adjustment mechanism often associated with rights issues. These findings inform investors and managers about expected price behavior around rights issue announcements and execution. The evidence supports monitoring cum-ex dates when planning trading strategies.